Neonatal Surgery: A Four-year Experience in a Teaching Hospital of Birgunj - Rai, Binod K; Yadav, Dhirendra P; Ansari, Mohammad A; Raya, Akash; Alam, Mohammad S; Sah, Chandrika (Journal of Institute of Medicine Nepal, 2022)
Introduction Neonatal surgery is one of the most challenging issues in medical field. The outcome of neonatal surgery is still poor in developing countries. The aim of this study was to report our experience regarding the etiological spectrum of neonatal surgical conditions and their outcome after surgical management. Methods A descriptive retrospective study which included all the neonatal cases that presented to Pediatric Surgery Department of National Medical College (NMC), Birgunj in the last four years. The data included in the study was from April 2017 to March 2021. Ethical clearance was obtained from the Institutional Review Committee of NMC (Reference No: F-NMC/563/078-079). All the neonates that underwent surgery were included in the study. A total of 68 cases were included in our study. Result A total 68 neonates were operated during the analyzed time period. Male to female ratio was 2.2:1. The age at presentation varied from 2 to 28 days and birth weight from 1.2 to 3.4 Kg. Anorectal malformation (ARM) (22, 32.3%) was the commonest cause of surgery followed by tracheo-esophageal fistula (TEF) (10, 14.7%) and pyloric stenosis (6, 8.8%). Mortality rate was 20.5% with septicemia as the commonest post operative complication. Conclusion The outcome of neonatal surgery in our center is not up to mark as compared with centers in developed countries. Early presentation of the patients, well equipped surgical neonatal intensive care facilities and trained manpower are needed to improve the outcome.